Performance analysis of dielectrically modulated InSb/Si TFET based label free biosensor. (November 2022) - Swain, Sukanta Kumar; Singh, Sangeeta; Sharma, Shashi Kant
Abstract: This work reports a novel structure of gate dielectric modulated SOI TFET for biological sensing applications. The device uses InSb/Si heterojunction with N+ pocket at drain channel junction. The nanocavity is caved between gate electrode and channel region towards drain side. InSb is used as a source material to enhance ON current. ATLAS TCAD is used to investigate electrical characteristics such as ambipolarity, energy band profile and sensitivity for better understanding of biosensing mechanism. The major advantage of the proposed structure is that it offers very low power consumption, high flexibility, portability, and sensitivity that can bring out new possibilities of developing very highly sensitive biosensors. The device exhibits excellent controllability over the channel and reduces the leakage current. The sensing of the biomolecules is based on ambipolar current which is dependent on the dielectric constant of nanocavity. Higher dielectric constant results in enhanced sensitivity of the device. Further, the device performance with 1/3 filled, 2/3 filled and fully filled cavity has also been investigated systematically. Highlights: The work investigates the sensitivity and selectivity of InSb/Si TFET based label free biosensor using Silvaco TCAD. InSb/Si based SOI TFET offers high ION /IOFF (from 10 11 ) and SSAVG (29.3). Higher sensitivity is achieved with higher dielectric constant. The simulation structure can be very useful for biosensing application.